Characteristics of Colombian inward foreign direct investment - Carlos Abreo; Eduardo Carrillo; Jennifer Pédussel Wu (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2023)
The research delves into the determinants of inward FDI to Colombia in the context of economic integration promoted by recent governments. Colombia's trade liberalisation, in addition to seeking to boost its trade flow, has focused on making the country more attractive to foreign direct investment (FDI), in a framework of fiscal discipline and a stable economic environment for economic growth, albeit characterised by complex institutional conditions. Government reforms have revitalized FDI inflows to Colombia, with the oil and mining sectors receiving the largest influx of new capital investments. Accordingly, this paper contributes to the literature with an analysis of the characteristics of FDI inflows to Colombia between 2007 and 2020 using an augmented gravity model approach. We find that stable government policies and the rule of law are key components in increasing FDI in Colombia and, more importantly, a bilateral investment treaty (BIT) significantly drives FDI into the country.
Keywords: F21; F36; O16; O54; C10; 330; FDI; Gravity Model; BITs; Colombia; Institutional quality; Labour competitiveness